LONG SOAKING OF CATFISH (Pangasius hypophthalmus) SKIN IN SEASONINGS ON CONSUMER ACCEPTANCE - Teddy Hario Pirmanda; Edison Edison; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aims to determine the effect of long soaking of catfish (Pangasius hypophthalmus) skin in seasonings on consumer acceptance, the treatments were K0 (without soaking), K1 (10 minutes soaking), K2 (20 minutes soaking), K3 (30 minutes soaking). Each treatment was carried out 3 (three) replications so that the experimental unit was 12 units. The parameters tested were organoleptic (color, aroma, flavor, and texture), and proximate analysis (water, protein, fat, and ash content). Based on the results of research conducted showing that the long soakingof catfish skin in seasoning had a very significant effect on the value of color, aroma and taste, however, had no significant effect on the texture. The best results were K3 treatment(30 minutes soaking) with 75 panelists (93.63%), The characteristics of skin were yellowish color (6.86), distinctive aroma of fish skin with a distinctive aroma of seasoning (7.25), typical taste of fish skin with seasonings (7.32crunchy and crisp texture (7.28). The proximate values of water, protein, fat, and ash content was 3.04%, 18.53%, 1.95%, and 4.95%, respectively. Keywords: fish skin, catfish, soaking long, seasoning